2017
DOI: 10.4014/jmb.1610.10012
|View full text |Cite
|
Sign up to set email alerts
|

Tilianin Inhibits MUC5AC Expression Mediated Via Down-Regulation of EGFR-MEK-ERK-Sp1 Signaling Pathway in NCI-H292 Human Airway Cells

Abstract: In the human airway, mucus exists to protect the respiratory system as a primary barrier of the innate immune system. However, hyperexpressed mucus limits airflow, resulting in a decrease of lung function. Among more than 20 mucin family members, MUC5AC and MUC5B are major glycoproteins in human airway mucus. The epidermal growth factor receptor (EGFR) signaling pathway is one of the mechanisms of these mucins expression and specificity protein-1 (Sp1) transcription factor is the downstream signal of this path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In this study, the expression levels of Muc5ac, p-ERK, and SP1 were significantly increased in the lung tissues of COPD mice. The result was associated with previous reports [ 34 , 35 ]. However, treatment with GFDHP significantly downregulated the expression levels of those proteins, indicating that GFDHP reduced mucus overproduction by inhibiting the ERK-SP1-Muc5ac pathway.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the expression levels of Muc5ac, p-ERK, and SP1 were significantly increased in the lung tissues of COPD mice. The result was associated with previous reports [ 34 , 35 ]. However, treatment with GFDHP significantly downregulated the expression levels of those proteins, indicating that GFDHP reduced mucus overproduction by inhibiting the ERK-SP1-Muc5ac pathway.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, as part of an ongoing search for potential anti-COPD agents, TN was used as a representative standardized compound of AR. In particular, it was previously reported that tilianin inhibited MUC5AC expression mediated via modulating the EGFR-MEK-ERK-Sp1 signaling pathway in human-airway epithelial cells [43], and effectively regulated inflammatory cytokines such as TNF-α, IL-1β, IL-18, and MCP-1 [44]. However, the mechanisms by which GG, AR, and their mixture inhibit neutrophilic lung inflammation has not been fully elucidated; in our study, we employed a murine COPD model for such purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, suppression of the production of MUC5AC may be a therapeutic method for secretory chronic airway inflammatory diseases (4). In our previous studies, mucosal airway hypersecretion was investigated in A549 lung adenocarcinoma cells, human NCI-H292 airway epithelial cells and normal human bronchial epithelial (NHBE) cells (33-35). In the present study, A549 alveolar only basal epithelial cells were used to investigate mucosal airway hypersecretion, owing to their high stability, medium culture conditions and low cost.…”
Section: Discussionmentioning
confidence: 99%